A statistical quality control study on Assistco Energy and Industrial Corporation - Garces, Mae Margaret; Santos, Gari Lenard; Sim Eleanor (Diliman, Quezon City College of Engineering, 2002)
Assistco Enrgy and Industrial Corporation Has been in the refractory industry for almost 30 years now. It is a major producer of refractory castables, under license from thermal Ceramics Inc, USA and distributor of other insulating materials. It has been the chief producer in petrochemical industries, rubber industry, sugar mills and steel manufacturing. The team conducts a statistical quality study on the company's main product, which is the dense and insulating castables. The four major castable series that have the greatest contribution to sales were the main focus of this study., which are the Kaolite 2500 LI, Kaolite 2300 LI, Kaocrete B and Kaocrete 28. an FMEA (Failure Mode and Effects Analysis) chart was constructed, with the aid of the production manager to examine potential failure modes of the process and product. Problem analysis was done and three quality problems were identified, incorrect formulation, improper mixing execution and impurity of raw material. The quality system of the company involves the raw material and finished goods inspection. both inspections require the samples to be tested in ITDI (Industrial Technology Development Institute). Provided with the necessary data, the team conducted the appropriate statistical process control tools in monitoring the process. Results of the control charts constructed indicates that the bulk density quality characteristic of the product is out of control in the later periods. This behavior is due to the humidity factor of the plant. Installation of exhaust or use of industrial fan is thus recommended. Improper mixing execution analysis was made and found to be the operator error as its root cause. A guideline and procedure manual is proposed to be posted beside the equipment for proper handling and manner of exacting the task. Raw materials were found to have impurities in them, hence the implementation of Military standard 105E is advised. The team also provided detailed action plans and implementation guidelines.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Assistco Energy and Industrial Coporation; Manufacturing industry; Quality control